Proceedings of the 12th Alcohol Hangover Research Group Meeting, in Buenos Aires, Argentina - Kristin Tellez-Monnery; Jessica Balikji; Lautaro Carrere; Analia Czerniczyniec; Lydia E. Devenney; Juan I. Guerra; Pantea Kiani; Silvia Lores-Arnaiz; Agnese Merlo; Ann-Kathrin Stock; Joris C. Verster; Analia Karadayian (Proceedings, 2024)
The current proceedings summarize the presentations held during the 12th meeting of the Alcohol Hangover Research Group (AHRG) in 2022, in Buenos Aires, Argentina. The aim of the annual AHRG meeting was to discuss advances in research on the causes, consequences, and possible treatment of the alcohol hangover, including methodological issues and the possibilities for future research collaboration.